The Effect of Exercise Trainings in the Stimulation of Brown Adipose Tissue and Transformation of White Adipose Tissue to Brite Adipose Tissue: A Review - Mohsen Jafari; Mehrdad Fathi; Elham Pouryamehr (Islamic Azad University, 2016)
There are three types of adipose tissue in the human body: white adipose tissue (WAT), brown adipose tissue (BAT) and beige or Brite adipose tissue. In WAT, energy reserves in the form of triglyceride, while in BAT triglyceride molecules lipolyze for thermogenesis through fatty acid oxidation. A protein called uncoupling protein-1 (UCP1) is responsible for non-shivering thermogenesis in BAT. The most important activators of BAT include peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α), sympathetic nervous system (SNS), hypothalamic-pituitary-thyroid axis (HPT axis), endothelium, atrial natriuretic peptides, irisin, β-aminoisobutyric acid (BAIBA), Fibroblast growth factor 21 (FGF21) and interleukin-6 (IL6) that generally exert their effects through stimulation of UCP1 expression and activity. Beige adipose are among white adipose and elevation of UCP1 gene expression is the main cause of their production that atrial natriuretic peptides, PGC1α, irisin, FGF21 and BAIBA are the most stimulators of this transformation. The role of exercise in the stimulation of BAT and transformation of WAT to Brite is discussed in this study.